Mind the gender gap : a mobilities perspective of sexual harassment on the London Underground - Lewis, Siân (Feminist Developments in Violence and Abuse, 2024)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. Drawing on women's lived experiences, Mind the Gender Gap offers an original approach to looking at sexual harassment on public transport in the UK, uncovering both the social and spatial factors that affect the perpetration of and reactions to sexual harassment on the London Underground. Examining sexual harassment on transport beyond limited analyses which lack discernment from 'public space' or a focus on rates of reporting, Siân Lewis introduces a novel conceptual framework built around the concepts of space, mobilities, rhythm and temporalities to reveal a new perspective at the intersection of mobility and feminist research on gendered violence. Honouring the multifaceted and nuanced experiences of sexual harassment by demonstrating how women anticipate, experience, react to and remember these incidents, Lewis attests that sexual harassment happens in a unique way in this often-neglected dimension of public space. How are these incidents located within gendered experiences in the city? How are acts of sexual harassment perpetrated? What key features define experiences of sexual harassment on public transport? How do these incidents impact women's mobilities over time? Written in the wake of the #MeToo movement, the Weinstein scandal, the global women's marches on Trump's inauguration day and a subsequent shift in public awareness and discourse, Mind the Gender Gap compliments, challenges and furthers our understanding of sexual harassment in public spaces.